Pugsley - Miles, Ellen (New York : Scholastic, 2007)
While working at her aunt's dog day care, Lizzie tries to help a pug puppy named Pugsley behave so he can find a new home.
"A Little Apple paperback."
3.7
3-6
Keywords: Dogs -- Juvenile fiction; Animal rescue -- Juvenile fiction; Animal welfare -- Juvenile fiction; Animals -- Infancy -- Juvenile fiction; Pets -- Juvenile fiction; Dogs -- Fiction; Animal rescue -- Fiction; Animal welfare -- Fiction; Animals -- Infancy -- Fiction; Pets -- Fiction; Dogs -- Fiction; Animal rescue -- Fiction; Animal welfare -- Fiction; Animal babies -- Fiction; Pets -- Fiction